The Shift to Visual News Consumption: Exploring Egyptian Users' Motivations, Behaviors, and Perceptions of News Values, Credibility, and Recognition on Instagram as a news Source. - Battah, Hussein (AUC Knowledge Fountain, 2025)
With the evolution of visual social media such as Instagram, news consumption and dissemination became different, focusing on Visual and Graphic content. With the current political and social-economic challenges in Egypt and the Region, such as The war in Gaza and the Egyptian economic crisis, the need for simple and immediate news updates became essential. Instagram has now satisfied that need among various users, specifically youth. This paper explores how consuming news over "Instagram" has influenced Egyptian users' perception of News Values and their definition of what to consider news. The paper also studies how several sources on Instagram have influenced users' perceptions of trust and how social cues on Instagram affect users' perceptions of the content. Employing the Uses and Gratifications theory as well as the News Values theory, this study surveyed online news consumers in Egypt where ( N=225 ) respondents participated; the aim of the survey is to test the Egyptian online news consumers' habits when consuming news over Instagram and to test how it affected their perception of News Values, News Recognition, and Trust.